SOLVING THE INVERSE KINEMATICAL PROBLEM OF A ROBOT ARM BY USING GROEBNER BASIS - Alisya Masturoh; Bambang Hendriya Guswanto; Triyani Triyani (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
The inverse kinematical problem of a robot arm is a problem to find some appropriate joint configurations for a pair of position and direction of a robot hand which is represented by a polynomial equations system. The system is solved by employing Groebner basis notion. Thus, the appropriate joint configurations for a pair of position and direction of the robot hand are obtained.